Optimal operation of cascade hydropower station based on interior point method - Shuai Feng; Yun Zhu (Energy Reports, 2022)
The optimal operation of cascade hydropower station is a hydropower system based on the optimal operation method of a single reservoir and considering the water relations between reservoirs. Based on the allocation capacity of the reservoir, Water resources are redistributed in cascade basins, so that the power generation can reach the maximum under the condition of limited water resources. The optimal operation of cascade hydropower stations is a nonlinear optimization problem with many variables and constraints. When solving nonlinear problems, this paper considers using interior point method, which has good robustness characteristics. In this paper, interior point method is used to solve the optimal operation of cascade hydropower stations with intermountain runoff flows into the reservoir. The method used in this paper can shorten the optimal operation calculation time of 24 h 4 reservoir cascade hydropower station to 0.16 s. Compared with the traditional manual operation calculation, the calculation in this paper can be used for online operation to realize real-time operation. The manually scheduled power generation and the calculated power generation are 4328MW and 4617.77MW. In the calculation result, the power generation is 6.7% more than that of the manual calculation result.